5th International Electronic Conference on Sensors and Applications 2018
DOI: 10.3390/ecsa-5-05755
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Characterization of Impulsive Underwater Noise Present in Port Facilities: Practical Case in the Port of Cartagena

Abstract: The data recording of underwater noise is a key aspect for the prevention and improvement of management systems of maritime spaces. Thus, due to the presence of activities potentially generating impulsive noise, ports deserve special attention. This article describes and shows the results of the spatial monitoring of both the basal noise and impulsive noise sources present in port facilities. A vessel was equipped with a smart digital hydrophone with a working frequency range between 10 and 200 kHz and an RVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For the matrix Y in (7), the remaining K d × M observations are typically not used as they contain the unknown data symbols. If the unknown data symbols are perfectly obtained, using the Bayes rule, the posterior mean of CIRs based on the prior probability in (17) and the channel measurement equation in (10) can be written by…”
Section: Noise-resistant Bayesian Channel Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the matrix Y in (7), the remaining K d × M observations are typically not used as they contain the unknown data symbols. If the unknown data symbols are perfectly obtained, using the Bayes rule, the posterior mean of CIRs based on the prior probability in (17) and the channel measurement equation in (10) can be written by…”
Section: Noise-resistant Bayesian Channel Estimationmentioning
confidence: 99%
“…The former type is presented in the background of the quiet deep sea, and exhibits a colored characteristic when approximated by Gaussian distribution, while for the site-specific noise, significant non-Gaussian components should be carefully considered [ 2 ]. Some experiments have confirmed that the noise is non-uniform across different locations, times and frequencies [ 17 ]. As a popular noise model in most UWA-OFDM systems, additive white Gaussian noise (AWGN) is straightforward for modeling and solving the noise distribution of the UWA channel, but it deviates from the actual underwater noise.…”
Section: Introductionmentioning
confidence: 99%